Water Front Advance Characatcristics in Vertisols under Surge Flow Irrigation - Reddy, K.S.; Singh, R.M.; Singh, D.K.; Rao, K.V.R.; Gharade, K.D. (Journal of Soil and Water Conservation, 2022)
A field experiment on surge irrigation and continuous mode was conducted to study the water front advance characteristics of vertisols and to standardize the surge parameters and furrow length for the design of a surge flow irrigation system. The experiment was conducted with 5, 10 and 15 min cycle time, 1/2 and % cycle ratio under inflow stream sizes of 1.5 and 2 1 so'. The study revealed that, there was an increase of 25% and 28.5% in water front advance in a furrow with % and % cycle ratios respectively under 1.5 1 s-' stream size and 15 min cycle time compared to 60 m of advance in continuous mode of water application. Similarly an increase of 16.2% and 25% was observed in 1/2 and % cycle ratio with 2 1 s-' stream size in 15 min cycle time compared to 67m of advance in continuous mode of water application. It was due to pre wetting and increased velocities in furrows. The study indicated that, a furrow length of 55 to 65 m is recommended for irrigation under combination of 1.5 1 s-' stream size, cycle time 15 min and cycle ratio of 1/2 under combination of 1.5 1 s-' stream size, cycle time 15 min and cycle ratio of 1/2 with 5-6 surge cycles. Similarly, a fun-ow length of 73 to 79 m Vbr as recommended under 2 1 so' with 4-6 surge cycles for achieving better water distribution uniformity in furrows.